(untitled) (Homoeopathy for All, 2023)
Eczema (atopic dermatitis) is a chronic inflammatory skin disease, which is characterized by chronic relapsing skin inflammation of flexural areas of the body, severe itch, and an aberrant immune response to environmental allergens. In this condition, an impairment of the skin barrier is the main reason leading to clinical manifestations such as marked dryness, itching, sensitivity to external irritants, and increased sensitivity to bacterial and viral infections. There has been a rising trend in the cases of Eczema especially in India, in the last four decades.1 It is noted that the environmental factors along with the genetic factors are the main causative factors of the disease. Family and twin studies revealed that up to 80% of eczema susceptibility can be linked to heritable factors, making the genome the target of attention